Analysis Of Factors Affecting Stroke Patients' Adherence To Treatment Programmes - Aty, Yoany Maria Vianney B.; Hammad, Hammad; Sambriongt, Maria (Poltekkes Kemenkes Banjarmasin, 2024)
Stroke occupies the first place as the deadliest disease in Indonesia. Data on the number of ischaemia stroke patients is 1117 patients. There are approximately 104 patients who do not make a return visit after being discharged from the hospital. The purpose of this study was to determine the factors that influence patient compliance with the treatment programme in outpatients with stroke. This study is a quantitative study with a crosectional research design. The sample determination in this study used total sampling of the average number of patient visits for 3 months. The number of samples taken was 63 patients. Statistical tests used in this study were chi square test and logistic regression test. Based on the results of the multivariate test, the variables that influence compliance with the treatment program for patients with ischaemia stroke are trust in health workers with a p-value of 0.000, family support with a p-value of 0.000, and self-efficacy with a p-value of 0.001. The conclusion of this study is that trust in health workers, family support and self-efficacy greatly affect the treatment program of patients with ischaemia stroke. The author hopes that families and health workers can provide good support and understanding to patients in following the existing treatment programme